Comparison of UV-LEDs and LPUV on inactivation and subsequent reactivation of waterborne fungal spores. (15th April 2020) - Wan, Qiqi; Wen, Gang; Cao, Ruihua; Xu, Xiangqian; Zhao, Hui; Li, Kai; Wang, Jingyi; Huang, Tinglin
Abstract: Recently, the contamination of fungi in water supply systems has been an area of increasing concern, such as Aspergillus spp. and Penicillium spp. It can cause some waterborne issues such as odor, taste and formation of mycotoxins. Ultraviolet light emitting diodes (UV-LEDs) are considered as a potential alternative to conventional mercury lamps for water disinfection. This study has compared the performance of LPUV (low pressure ultraviolet) and UV-LEDs with emissions at 265, 280 nm and combination emissions at 265/280 nm to test inactivation efficiency, reactivation, viability and electrical energy consumption in the treatment of three water-borne fungal species ( Aspergillus niger, Penicillium polonicum, Trichoderma harzianum ) at a batch water disinfection system. The results showed that the performances of UV-LEDs were superior for the inactivation of fungal spores compared to the 254 nm (LP), while no statistically differences were observed among the UV-LEDs (p > 0.05). The average photoreactivation rate ( k 1 ) of fungal spores irradiated by UV-LEDs and 254 nm (LP) follows the order: T. harzianum > A. niger > P. polonicum . Compared with LPUV, UV-LEDs irradiation at 280 nm and 265/280 nm more efficiently inhibits photoreactivation, which was attributed to that irradiation of 280 nm and 265/280 nm would cause greater membrane damage and increase intracellular reactive oxygen species level of fungal spores according to the flow cytometric results. The electrical energy consumption of UV-LEDs was higher than that of LPUV, which was due to its lower wall plug efficiency. The results of this study can provide additional and beneficial information for the reasonable exploitation of UV-LEDs in water disinfection. Graphical abstract: Image 1 Highlights: UV-LEDs are efficient in inactivation of fungal spores. UV-LEDs irradiation at 280 nm could control the photoreactivation of fungi more efficiently. UV-LEDs emitting at 280 and 265/280 nm could cause more serious membrane damage of fungal spores. UV-LEDs of three wavelengths could increase intracellular ROS of fungal spores obviously. The electrical energy consumption of UV-LEDs was higher than that of LPUV.